Secondary battery and electric device

By designing two layers of active material on the positive electrode sheet of lithium iron phosphate battery and maintaining the high content of ethyl propionate in the electrolyte, the problem of poor circulation performance of the battery under high temperature conditions and serious lithium evolution phenomenon is solved, and excellent circulation capacity retention rate and low lithium evolution risk are achieved.

CN119786532AActive Publication Date: 2025-04-08SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411986370.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, lithium iron phosphate batteries have poor circulation performance under high temperature conditions (45°C), fast capacity attenuation, and obvious lithium evolution phenomenon, especially when the EP content of ethyl propionate in the electrolyte is ≥45 wt.%. The problem is more prominent.

Method used

A secondary battery is designed, and the positive electrode sheet includes two layers of active material: a first positive electrode active material layer and a second positive electrode active material layer. The molar ratio and mass percentage of iron and phosphorus elements of the two layers of materials are different, and the mass percentage of ethyl propionate is maintained in the electrolyte ≥45%.

Benefits of technology

Through this design, the battery's circulation capacity retention rate under high temperature conditions (45°C) is significantly improved, the lithium evolution phenomenon is reduced, and the circulation performance is excellent, while maintaining high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222969370000131
    Figure BDA0005222969370000131
  • Figure BDA0005222969370000141
    Figure BDA0005222969370000141
  • Figure BDA0005222969370000142
    Figure BDA0005222969370000142
Patent Text Reader

Abstract

The invention discloses a secondary battery and an electric device, and belongs to the technical field of batteries. According to the secondary battery provided by the invention, the first positive electrode active material layer is arranged on at least one surface of the positive electrode current collector, and the second positive electrode active material layer is arranged on the surface of the first positive electrode active material layer; the molar ratio P1 of the iron element and the phosphorus element in the first positive electrode active material layer is limited to be smaller than the molar ratio P2 of the iron element and the phosphorus element in the second positive electrode active material layer; the first lithium iron phosphate compound and the second lithium iron phosphate respectively and independently comprise titanium and / or vanadium; therefore, the problems of poor cycle performance under a high-temperature condition and obvious lithium precipitation phenomenon in the cycle process caused by high power of the secondary battery due to the fact that the mass percentage of ethyl propionate in the electrolyte is greater than or equal to 45% can be effectively solved; the secondary battery provided by the invention has relatively high capacity, excellent high-temperature cycle performance and low lithium precipitation risk in the cycle process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and in particular relates to a secondary battery and an electrical device. Background Art

[0002] Lithium iron phosphate with high kinetic electrolyte (ethyl propionate EP content ≥ 45wt.%) is prone to lithium deposition and rapid capacity decay during the 45℃ / 3C cycle process. By disassembling the lithium iron phosphate cycle battery, it is generally easy to have a lithium deposition interface at 1500-1800 cycles. At present, the main way to solve the above problems is to reduce the compaction density of the negative electrode, use soft carbon or hard carbon coating to improve the kinetic performance of the negative electrode and optimize the electrolyte formula, but it cannot be completely solved, because as the cycle progresses, the decomposition of the electrolyte intensifies, forming more side reaction products, the polarization of the battery gradually increases, and the overpotential on both sides of the positive electrode gradually increases. Summary of the invention

[0003] The purpose of this application is to solve the problem that the content of ethyl propionate EP added to the electrolyte in the prior art

[0004] ≥45wt.% to improve the kinetics of the secondary battery, which will cause the capacity of the secondary battery to decay too quickly. A secondary battery and an electrical device with excellent cycle capacity retention rate and no obvious lithium plating phenomenon under high temperature conditions (45°C) are provided.

[0005] To achieve the above-mentioned object, in a first aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a first positive electrode active material layer and a second positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the first positive electrode active material layer is arranged between the positive electrode current collector and the second positive electrode active material layer;

[0006] The first positive electrode active material layer includes a first lithium iron phosphate compound, and the second positive electrode active material layer includes a second lithium iron phosphate compound;

[0007] The first lithium iron phosphate compound and the second lithium iron phosphate each independently include a first element;

[0008] The first element includes titanium and / or vanadium;

[0009] The molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is less than the molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer;

[0010] The mass percentage W1 of the first element in the first lithium iron phosphate compound is less than the mass percentage W2 of the first element in the second lithium iron phosphate compound;

[0011] The electrolyte includes ethyl propionate, and the mass percentage of the ethyl propionate is ≥45% based on the total mass of the electrolyte.

[0012] As an implementation scheme of the present application, the 0.005≤P2-P1≤0.025.

[0013] As an embodiment of the present application, the 900ppm≤W2-W1≤2000ppm.

[0014] As an embodiment of the present application, the first element includes titanium and vanadium; the mass percentage Ti1 of titanium in the first lithium iron phosphate compound is less than the mass percentage Ti2 of titanium in the second lithium iron phosphate compound;

[0015] The mass percentage V1 of vanadium in the first lithium iron phosphate compound is less than the mass percentage V2 of vanadium in the second lithium iron phosphate compound.

[0016] As an embodiment of the present application, the 400ppm≤Ti2-Ti1≤1000ppm.

[0017] As an embodiment of the present application, the 400ppm≤V2-V1≤1200ppm.

[0018] As an embodiment of the present application, a molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is 0.950 to 0.975.

[0019] As an embodiment of the present application, a molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer is 0.955 to 1.000.

[0020] As an embodiment of the present application, the mass percentage Ti1 of titanium in the first lithium iron phosphate compound is 200 to 5000 ppm.

[0021] As an embodiment of the present application, the mass percentage Ti2 of titanium in the second lithium iron phosphate compound is 600 to 6000 ppm.

[0022] As an embodiment of the present application, the mass percentage V1 of vanadium in the first lithium iron phosphate compound is 200 to 3000 ppm.

[0023] As an embodiment of the present application, the mass percentage V2 of vanadium in the second lithium iron phosphate compound is 600 to 4000 ppm.

[0024] As an embodiment of the present application, the single-side thickness of the first positive electrode active material layer is 10 to 60 μm.

[0025] As an embodiment of the present application, the thickness of the second positive electrode active material layer is 10 to 60 μm.

[0026] As an embodiment of the present application, the difference between the compaction density PD2 of the second positive electrode active material layer and the compaction density PD1 of the first positive electrode active material layer is 0.1 g / cm 3 ≤PD2-PD1≤0.15g / cm 3 .

[0027] As an embodiment of the present application, the compaction density PD1 of the first positive electrode active material layer is 1.50 to 3.00 g / cm 3 .

[0028] As an embodiment of the present application, the compaction density PD2 of the second positive electrode active material layer is 1.60 to 3.15 g / cm 3 .

[0029] In a second aspect of the present application, an electrical device is provided, comprising the secondary battery described above.

[0030] The beneficial effects of this application are:

[0031] The secondary battery provided by the present application comprises a first positive electrode active material layer on at least one surface of a positive electrode current collector, and a second positive electrode active material layer arranged on the surface of the first positive electrode active material layer and away from the positive electrode current collector, and the molar ratio of iron element to phosphorus element in the first positive electrode active material layer P1 is limited to the molar ratio of iron element to phosphorus element in the second positive electrode active material layer P2, and the first lithium iron phosphate compound and the second lithium iron phosphate each independently comprise titanium and / or vanadium; thereby effectively solving the problem of poor cycle performance under high temperature conditions caused by the high power of the secondary battery due to the mass percentage of ethyl propionate ≥45% in the electrolyte; the secondary battery provided by the present application has a high capacity and a good cycle capacity retention rate, that is, excellent cycle performance. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific embodiments.

[0033] Unless otherwise specified, the reagents, methods and equipment used in this application are conventional reagents, methods and equipment in the art.

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0036] In the present application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. In one embodiment of the present application, the present application provides a secondary battery, including a positive electrode plate, a negative electrode plate, a separator and an electrolyte, the positive electrode plate including a positive electrode collector and a first positive electrode active material layer and a second positive electrode active material layer disposed on at least one surface of the positive electrode collector, the first positive electrode active material layer being disposed between the positive electrode collector and the second positive electrode active material layer;

[0037] The first positive electrode active material layer includes a first lithium iron phosphate compound, and the second positive electrode active material layer includes a second lithium iron phosphate compound;

[0038] The first lithium iron phosphate compound and the second lithium iron phosphate each independently include a first element;

[0039] The first element includes titanium and / or vanadium;

[0040] The molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is less than the molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer;

[0041] The mass percentage W1 of the first element in the first lithium iron phosphate compound is less than the mass percentage W2 of the first element in the second lithium iron phosphate compound;

[0042] The electrolyte includes ethyl propionate, and the mass percentage of the ethyl propionate is ≥45% based on the total mass of the electrolyte.

[0043] The secondary battery provided by the present application is provided with a first positive electrode active material layer on at least one surface of a positive electrode current collector, and a second positive electrode active material layer provided on the surface of the first positive electrode active material layer and away from the positive electrode current collector, and the molar ratio of iron element to phosphorus element in the first positive electrode active material layer P1 is limited to the molar ratio of iron element to phosphorus element in the second positive electrode active material layer P2, and the first lithium iron phosphate compound and the second lithium iron phosphate each independently include titanium and / or vanadium; thereby effectively solving the problems of poor cycle performance under high temperature conditions and obvious lithium deposition during the cycle caused by the mass percentage of ethyl propionate ≥45% in the electrolyte and the high power of the secondary battery; the secondary battery provided by the present application has a good high temperature (45°C) cycle capacity retention rate while having a high capacity, that is, excellent high temperature cycle performance and low risk of lithium deposition during the cycle.

[0044] Specifically, in the first aspect, the design of the first positive electrode active material layer makes the reaction activity of the first positive electrode active material layer slightly lower, has higher safety, and can reduce the structural damage and interface side reactions during high temperature cycles. The increase in CEI interface and phase transfer impedance. In the second aspect, the design of the second positive electrode active material layer can effectively improve the wettability, kinetics, and bulk and surface structural stability of the positive electrode plate, reduce the growth of side reactions and SEI interface and phase transfer impedance between the surface of the positive electrode plate and the electrolyte, and reduce the increase in diffusion impedance between the positive electrode plate and the negative electrode plate, thereby significantly reducing the risk of lithium precipitation of the negative electrode plate during high temperature cycles; at the same time, the design of the second positive electrode active material layer can also inhibit the dissolution of iron elements in lithium iron phosphate during long-term high current cycles. In the third aspect, when the first lithium iron phosphate compound and the second lithium iron phosphate independently include titanium and / or vanadium, it can not only increase the interlayer spacing of lithium iron phosphate, but also improve the bulk and surface structural stability and conductivity of lithium iron phosphate, improve the kinetics of lithium iron phosphate, and increase the capacity of the secondary battery. Combining the above three aspects, the secondary battery provided in the present application has excellent kinetics, no obvious lithium plating during high-temperature fast-charging cycles, and a high cycle capacity retention rate, that is, it has a high capacity and excellent high-temperature cycle performance.

[0045] It should be noted that the method for testing and calculating the molar ratio of iron and phosphorus in the first positive electrode active material layer and the second positive electrode active material includes the following steps: using ICP to test the content of iron and phosphorus in different coating powders respectively, and then converting them into molar ratios.

[0046] It should be noted that the testing method for the mass percentage of the first element in the first lithium iron phosphate compound and the second lithium iron phosphate compound includes the following steps: using ICP to test the molar content of the first element in different coating powders, respectively, and then converting it into the mass and mass fraction of the first element, the mass percentage of the first element in the lithium iron phosphate compound = the mass of the first element in the lithium iron phosphate compound / the mass of the lithium iron phosphate compound.

[0047] It should be noted that the test method for the mass percentage of ethyl propionate in the electrolyte includes the following steps: taking a certain amount of electrolyte sample and calibrating the characteristic peak area of ​​ethyl propionate EP through liquid chromatography, and then converting it into the mass fraction of ethyl propionate EP (mass fraction of ethyl propionate EP = mass of EP / solvent + mass of non-lithium salt additives).

[0048] In one embodiment, based on the total mass of the electrolyte, the mass percentage of the ethyl propionate is 45-70%.

[0049] Exemplarily, based on the total mass of the electrolyte, the mass percentage of ethyl propionate can be any point value or any two point range values ​​between 45% and 70%, for example, it can be one of 45%, 50%, 55%, 60%, 65%, 70% or any two range values.

[0050] In one embodiment, 0.005≤P2-P1≤0.025.

[0051] Exemplarily, P2-P1 may be any point value or any two point range values ​​between 0.005 and 0.025, for example, it may be one of 0.005, 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, 0.02, 0.022, 0.024, 0.025 or any two range values.

[0052] The research in this application found that when the difference between the molar ratio P2 of iron and phosphorus in the second positive electrode active material layer and the molar ratio P1 of iron and phosphorus in the first positive electrode active material layer is further selected to be between 0.005 and 0.025, the bulk and surface structural stability of the positive electrode plate can be better improved, the side reactions and polarization of the battery during high-temperature cycling can be reduced, the risk of lithium plating of the negative electrode plate can be reduced, and the dissolution of iron in the cycling process can be inhibited; thereby effectively improving the cycling performance of the secondary battery at high temperatures.

[0053] In one embodiment, the 900 ppm≤W2-W1≤2000 ppm.

[0054] Exemplarily, the W2-W1 may be any point value or any two point range values ​​between 900ppm≤W2-W1≤2000ppm, for example, it may be one of 900ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm or any two range values.

[0055] The present application study found that when the difference between the mass percentage W2 of the first element in the second lithium iron phosphate compound and the mass percentage W1 of the first element in the first lithium iron phosphate compound is between 900 and 2000 ppm, the bulk and surface structural stability of the positive electrode plate can be better improved, the conductivity of the system can be enhanced, and thus the high temperature cycle performance and capacity of the secondary battery can be improved.

[0056] In one embodiment, the first element includes titanium and vanadium;

[0057] The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is less than the mass percentage Ti2 of titanium in the second lithium iron phosphate compound;

[0058] The mass percentage V1 of vanadium in the first lithium iron phosphate compound is less than the mass percentage V2 of vanadium in the second lithium iron phosphate compound.

[0059] The present application has found that when the first elements of the first lithium iron phosphate compound and the second lithium iron phosphate compound both include titanium and vanadium, and the mass percentages of titanium and vanadium in the first lithium iron phosphate compound and the second lithium iron phosphate compound satisfy the relationship of the present application, it is possible to increase the interlayer spacing of lithium iron phosphate while improving the bulk and surface structural stability and conductivity of lithium iron phosphate, improve the kinetics of lithium iron phosphate and the lithium precipitation phenomenon of the positive electrode sheet; thereby effectively improving the capacity, high temperature cycle performance and fast charging performance of the secondary battery.

[0060] In one embodiment, the 400ppm≤Ti2-Ti1≤1000ppm.

[0061] Exemplarily, the Ti2-Ti1 may be any point value or any two point range values ​​between 400 and 1000 ppm, for example, it may be one or any two range values ​​of 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, and 1000 ppm.

[0062] In one embodiment, the 400 ppm≤V2-V1≤1200 ppm.

[0063] Exemplarily, the V2-V1 may be any point value or any two point range values ​​between 400 and 1000 ppm, for example, it may be one or any two range values ​​of 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm.

[0064] The present application has found that when the first elements of the first lithium iron phosphate compound and the second lithium iron phosphate compound both include titanium and vanadium, and the difference in mass percentage of titanium and vanadium in the first lithium iron phosphate compound and the second lithium iron phosphate compound is within the above range, the comprehensive performance of the obtained secondary battery is better.

[0065] In one embodiment, the molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is 0.950-0.975.

[0066] Illustratively, the molar ratio P1 of iron to phosphorus in the first positive electrode active material layer may be any point value or any two point range values ​​between 0.950 and 0.975, for example, it may be one of 0.950, 0.952, 0.954, 0.956, 0.958, 0.960, 0.962, 0.964, 0.966, 0.968, 0.970, 0.972, 0.975 or any two range values.

[0067] In one embodiment, the molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer is 0.955-1.000.

[0068] Exemplarily, the molar ratio P2 of iron element to phosphorus element in the second positive electrode active material layer may be any point value or any two point range values ​​between 0.955 and 1.000, for example, it may be one of 0.955, 0.960, 0.965, 0.970, 0.975, 0.980, 0.985, 0.990, 0.995, 1.000 or any two range values.

[0069] The present application study found that when the molar ratio P1 of iron and phosphorus in the first positive electrode active material layer and the molar ratio P2 of iron and phosphorus in the second positive electrode active material layer are within the above range, the difference between P2-P1 is more conducive to the bulk and surface structural stability and impedance growth of the overall inner active coating and the surface active coating lithium iron phosphate.

[0070] In one embodiment, the mass percentage Ti1 of titanium in the first lithium iron phosphate compound is 200-5000 ppm.

[0071] Exemplarily, the mass percentage Ti1 of titanium in the first lithium iron phosphate compound may be any point value or any two point range values ​​between 200 and 5000 ppm, for example, it may be one of 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm or any two range values.

[0072] In one embodiment, the mass percentage Ti2 of titanium in the second lithium iron phosphate compound is 600-6000 ppm.

[0073] Exemplarily, the mass percentage Ti2 of titanium in the second lithium iron phosphate compound can be any point value between 600 and 6000 ppm or any two point range values, for example, it can be one of 600 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, 5500 ppm, 6000 ppm or any two range values.

[0074] In one embodiment, the mass percentage V1 of vanadium in the first lithium iron phosphate compound is 200-3000 ppm.

[0075] Exemplarily, the mass percentage V1 of vanadium in the first lithium iron phosphate compound may be any point value or any two point range values ​​between 200 and 3000 ppm, for example, it may be one of 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm or any two range values.

[0076] In one embodiment, the mass percentage V2 of vanadium in the second lithium iron phosphate compound is any point value or any two point range values ​​between 600 and 4000 ppm, for example, it can be one of 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 2000 ppm, 3000 ppm, 3600 ppm, 4000 ppm or any two range values.

[0077] The present application study found that when the mass percentages of titanium and vanadium in the first lithium iron phosphate compound and the second lithium iron phosphate compound are respectively within the above ranges, the difference between W2-W1 is more conducive to the bulk and surface structural stability and impedance growth of the overall inner active coating and the surface active coating lithium iron phosphate, the cycle capacity retention rate is better, and the negative electrode lithium deposition interface is also slightly better.

[0078] In one embodiment, the single-side thickness of the first positive electrode active material layer is 10-60 μm.

[0079] It should be noted that the single-side thickness of the first positive electrode active material layer is tested by SEM testing.

[0080] Exemplarily, the single-sided thickness of the first positive electrode active material layer may be any point value or any two point range values ​​between 10 and 60 μm, for example, it may be one of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm or any two range values.

[0081] In one embodiment, the thickness of the second positive electrode active material layer is 10-60 μm.

[0082] It should be noted that the thickness of the second positive electrode active material layer is tested by SEM testing.

[0083] Exemplarily, the thickness of the second positive electrode active material layer may be any point value or any two point range values ​​between 10 and 60 μm, for example, it may be one of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm or any two range values.

[0084] The present application has found that when the single-sided thickness of the first positive electrode active material layer and the thickness of the second positive electrode active material layer are further selected to be within the above ranges, the 45°C cycle performance of the battery is better and lithium plating is less.

[0085] In one embodiment, the difference between the compaction density PD2 of the second positive electrode active material layer and the compaction density PD1 of the first positive electrode active material layer is 0.1 g / cm 3 ≤PD2-PD1≤0.15g / cm 3 .

[0086] It should be noted that the test method for the compaction density PD2 of the second positive electrode active material layer and the compaction density PD1 of the first positive electrode active material layer is: the thickness of each coating is calibrated by SEM+CP, and the specific values ​​of PD1 and PD2 are converted by the powder weight corresponding to the PD1 and PD2 coatings.

[0087] For example, the difference between the compaction density PD2 of the second positive electrode active material layer and the compaction density PD1 of the first positive electrode active material layer may be 0.1 to 0.15 g / cm 3 Any point value or any range value between two points, for example, 0.1g / cm3 , 0.11g / cm 3 , 0.12g / cm 3 , 0.13g / cm 3 , 0.14g / cm 3 , 0.15g / cm 3 One or any two range values ​​in .

[0088] The research in this application found that when the difference between the compaction density PD2 of the second positive electrode active material layer and the compaction density PD1 of the first positive electrode active material layer is within the above range, the difference PD2-PD1 is more conducive to the bulk and surface structural stability and impedance growth of the overall inner active coating and the surface active coating lithium iron phosphate, the cycle capacity retention rate is better, and the negative electrode lithium plating interface is also slightly better.

[0089] In one embodiment, the compaction density PD1 of the first positive electrode active material layer is 1.50-3.00 g / cm 3 .

[0090] For example, the compaction density PD1 of the first positive electrode active material layer may be 1.50 to 3.00 g / cm 3 Any point value or any range value between two points, for example, 1.5g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.6g / cm 3 , 2.8g / cm 3 、3.0g / cm 3 One or any two range values ​​in .

[0091] In one embodiment, the compaction density PD2 of the second positive electrode active material layer is 1.60-3.15 g / cm 3 .

[0092] For example, the compaction density PD2 of the second positive electrode active material layer may be 1.60 to 3.15 g / cm 3 Any point value or any range value between two points, such as 1.6g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.6g / cm 3 , 2.8g / cm 3 、3.0g / cm3 、3.15g / cm 3 One or any two range values ​​in .

[0093] The research in this application found that when the compaction density PD1 of the first positive electrode active material layer and the compaction density PD2 of the second positive electrode active material layer are further selected within the above range, the difference PD2-PD1 is more conducive to the bulk and surface structural stability and impedance growth of the overall inner active coating and the surface active coating lithium iron phosphate, the cycle capacity retention rate is better, and the negative electrode lithium deposition interface is also slightly better.

[0094] In one embodiment, the first positive electrode active material layer and the second positive electrode active material layer further include a conductive agent and a positive electrode binder. The present application has no limitation on the conductive agent and the positive electrode binder, and any known conductive agent and positive electrode binder can be used.

[0095] Exemplarily, the conductive agent includes conductive graphite; and the positive electrode binder includes polyvinylidene fluoride.

[0096] In one embodiment, the positive electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of electrical conduction and current collection. In one embodiment, the positive electrode current collector may be made of a metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector is made of aluminum foil or carbon-coated aluminum foil.

[0097] In one embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material. The present application has no limitation on the negative electrode active material, and any known negative electrode active material can be used. As an example, the negative electrode active material can be at least one of artificial graphite, natural graphite, silicon-carbon composite material, silicon alone, silicon oxide, and hard carbon.

[0098] In one embodiment, the negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of conducting electricity and collecting current. In one embodiment, the negative electrode current collector may be made of a metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector is made of copper foil.

[0099] In one embodiment, the electrolyte further comprises an organic solvent and a lithium salt. The present application has no limitation on the organic solvent and the lithium salt in the electrolyte, and any known organic solvent and lithium salt can be used.

[0100] Exemplarily, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate; the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0101] In one embodiment, the separator of the secondary battery is disposed between the positive electrode and the negative electrode.

[0102] In one embodiment of the present application, the present application proposes an electrical device, and the electrical device includes the secondary battery described in the present application.

[0103] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0104] Example 1

[0105] The present invention provides a secondary battery, wherein a method for preparing the secondary battery comprises the following steps:

[0106] (1) Preparation of positive electrode sheet

[0107] S1, a first lithium iron phosphate compound (a molar ratio of iron to phosphorus P1 is 0.96, a mass percentage of titanium Ti1 is 1000 ppm, and a mass percentage of vanadium V1 is 500 ppm), conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 95.0:3.5:1.5 to obtain a first positive electrode active material layer slurry;

[0108] S2, a second lithium iron phosphate compound (a molar ratio of iron to phosphorus P2 is 0.98, a mass percentage of titanium Ti2 is 1800 ppm, and a mass percentage of vanadium V2 is 1000 ppm), conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 95.0:3.5:1.5 to obtain a second positive electrode active material layer slurry;

[0109] S3, coating the first positive electrode active material layer slurry on both sides of the positive electrode current collector aluminum foil to obtain a first positive electrode active material layer with a single-side thickness of 30 μm, then coating the second positive electrode active material layer slurry on the surface of the first positive electrode active material layer to obtain a second positive electrode active material layer with a single-side thickness of 30 μm; then drying, rolling, slitting and cutting to obtain a positive electrode sheet;

[0110] (2) Preparation of negative electrode sheet

[0111] Artificial graphite, conductive carbon black (SP), binder (sodium carboxymethyl cellulose) and styrene-butadiene rubber are mixed evenly in a mass ratio of 97:0.5:1.2:1.3, and then water is added to the above mixture in batches and continued to be fully mixed and stirred to prepare negative electrode slurry, and then the homogeneous negative electrode slurry is evenly coated on both sides of a 6μm copper foil, and after drying, rolling, slitting and cutting, a negative electrode sheet is obtained;

[0112] (3) Preparation of electrolyte

[0113] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), ethyl propionate (EP), vinylene carbonate (VC), 1,3-propane sultone (PS), vinyl sulfate (DTD), and tris(trimethylsilyl) phosphate (TMSP) are mixed in a mass ratio of 20:30:45:3:1:0.5:0.5, and then lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI are added; wherein the molar concentration of LiPF6 in the electrolyte is 0.5M, and the molar concentration of LiFSI is 0.7M;

[0114] (4) Preparation of secondary batteries

[0115] The prepared positive electrode sheet, negative electrode sheet, separator and other battery components are assembled, and a secondary battery is obtained through processes such as shaping, baking, packaging, liquid injection, formation, and capacity division.

[0116] Embodiments 2 to 5

[0117] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the molar ratio of the iron element to the phosphorus element is changed by adjusting the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0118] Embodiments 6 to 9

[0119] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the mass percentage of the titanium element is changed by adjusting the addition of the titanium element in the first element of the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0120] Embodiments 10 to 13

[0121] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the mass percentage of the vanadium element is changed by adjusting the addition of the vanadium element in the first element of the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0122] Embodiments 14 to 15

[0123] The embodiment of the present application provides a secondary battery, which is different from the embodiment 1 in that the parameters in Tables 1 to 2 are achieved by adjusting the type and addition amount of the first element of the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0124] Embodiments 16 to 17

[0125] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the parameters in Tables 1 to 2 are achieved by adjusting the coating thickness of the first positive electrode active material layer and the second positive electrode active material layer.

[0126] Embodiments 18 to 20

[0127] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the compaction density of the first positive electrode active material layer and the second positive electrode active material layer is changed by adjusting the coating weight.

[0128] Embodiment 21

[0129] The embodiment of the present application provides a secondary battery. The difference between the secondary battery and the embodiment 1 is that the mass percentage of ethyl propionate is changed by adjusting the addition of ethyl propionate in the electrolyte.

[0130] Comparative Example 1

[0131] The comparative example of the present application provides a secondary battery, which is different from Example 1 in that the molar ratio of the iron element to the phosphorus element is changed by adjusting the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0132] Comparative Examples 2-3

[0133] The comparative example of the present application provides a secondary battery, which is different from Example 1 in that the parameters in Tables 1 to 2 are achieved by adjusting the addition of the first element in the first lithium iron phosphate compound and the second lithium iron phosphate compound.

[0134] Comparative Example 4

[0135] The comparative example of the present application provides a secondary battery, which is different from the embodiment 1 in that the mass percentage of ethyl propionate is changed by adjusting the addition of ethyl propionate in the electrolyte.

[0136] The molar ratio of iron to phosphorus in the first positive electrode active material layer P1 and the molar ratio of iron to phosphorus in the second positive electrode active material layer P2 and the difference between the two P2-P1 in the embodiments and comparative examples, the mass percentage of titanium in the first lithium iron phosphate compound Ti1 / ppm and the mass percentage of titanium in the second lithium iron phosphate compound Ti2 / ppm and the difference between the two Ti2-Ti1, the mass percentage of vanadium in the first lithium iron phosphate compound V1 / ppm and the mass percentage of vanadium in the second lithium iron phosphate compound V2 / ppm and the difference between the two V2-V1, the mass percentage of the first element in the second lithium iron phosphate compound W2 / ppm and the difference W2-W1 of the mass percentage of the first element in the first lithium iron phosphate compound W1 / ppm, the single-sided thickness of the first positive electrode active material layer d1 / μm, the thickness of the second positive electrode active material layer d2 / μm, the compaction density of the first positive electrode active material layer PD1 / g / cm 3 and the compaction density PD2 / g / cm2 of the second positive electrode active material layer 3 The difference between the two, PD2-PD1, and the mass percentage Y / % of ethyl propionate in the electrolyte are shown in Tables 1-2;

[0137] Table 1 Secondary battery parameters

[0138]

[0139]

[0140] Table 2 Secondary battery parameters

[0141]

[0142]

[0143] The cycle performance, capacity and lithium precipitation of the secondary batteries prepared in the embodiment and the comparative example are shown in Table 3; wherein the test method comprises the following steps:

[0144] 1) Capacity: 25±5℃, every 100cls, collect the following capacity, 1C discharge to 2.0V, then 1C charge to 3.6V, cut-off current 0.05C, 1C discharge to 2.0V; 1C=4.4A);

[0145] 2) Cycle performance: 45℃±5℃, 1cls process (3C charge to 3.6V, cut-off current 0.05C, 3C discharge to 2.0V, 1h interval between charge and discharge; 1C=4.4A); record the 25℃ / 1C capacity retention rate at 1800 cycles;

[0146] 3) Lithium deposition: 1C full charge to 3.6V, cut-off current 0.05C, then disassembled in a drying room. After disassembly, the negative electrode interface is placed under an electron microscope for observation. According to the proportion of lithium deposition area (expressed by S), the degree of lithium deposition is divided into the following levels;

[0147] No lithium precipitation: S≤1%;

[0148] Slight lithium deposition: 1%<S≤10%;

[0149] Moderate lithium precipitation: 10%<S≤20%;

[0150] Severe lithium deposition: 20%<S≤40%;

[0151] Severe lithium precipitation: S>40%.

[0152] Table 3 Secondary battery performance data

[0153]

[0154]

[0155] It can be seen from Table 3 that the technical solution provided by the present application has a high capacity, excellent cycle performance and a low risk of lithium deposition; specifically, the capacity of the obtained secondary battery is above 3820 mAh, the cycle retention rate is above 86.3%, and after disassembly and observation after the cycle, it is found that the lithium deposition is no lithium deposition or slight lithium deposition;

[0156] The results of Examples 1 to 21 of the present application and Comparative Example 1 show that when the molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is greater than the molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer, the capacity of the obtained secondary battery shows a significant downward trend, and the cycle performance also decreases, and the lithium precipitation phenomenon of the negative electrode plate is more obvious; the results of Examples 1 to 21 of the present application and Comparative Example 2 show that when the mass percentage W1 of the first element in the first lithium iron phosphate compound is greater than the mass percentage W2 of the first element in the second lithium iron phosphate compound, the capacity of the obtained secondary battery shows a significant downward trend, and the cycle performance also decreases, and the lithium precipitation phenomenon of the negative electrode plate is also more obvious; the results of Examples 1 to 21 of the present application and Comparative Example 3 show that when the first element is not added to the first lithium iron phosphate and the second lithium iron phosphate compounds, the capacity and cycle performance of the obtained secondary battery are significantly reduced, and severe lithium precipitation will occur; the results of Examples 1 to 21 of the present application and Comparative Example 4 show that when the mass percentage of ethyl propionate in the electrolyte is less than 45%, the capacity and cycle performance of the obtained secondary battery are significantly reduced.

[0157] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a first positive electrode active material layer and a second positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the first positive electrode active material layer is disposed between the positive electrode current collector and the second positive electrode active material layer; The first positive electrode active material layer includes a first lithium iron phosphate compound, and the second positive electrode active material layer includes a second lithium iron phosphate compound; The first lithium iron phosphate compound and the second lithium iron phosphate each independently include a first element; The first element includes titanium and / or vanadium; The molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is less than the molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer; The mass percentage W1 of the first element in the first lithium iron phosphate compound is less than the mass percentage W2 of the first element in the second lithium iron phosphate compound; The electrolyte includes ethyl propionate, and the mass percentage of the ethyl propionate is ≥45% based on the total mass of the electrolyte.

2. The secondary battery according to claim 1, characterized in that: The 0.005≤P2-P1≤0.

025.

3. The secondary battery according to claim 1, characterized in that: The 900ppm≤W2-W1≤2000ppm.

4. The secondary battery according to claim 1, characterized in that: The first element includes titanium and vanadium; The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is less than the mass percentage Ti2 of titanium in the second lithium iron phosphate compound; The mass percentage V1 of vanadium in the first lithium iron phosphate compound is less than the mass percentage V2 of vanadium in the second lithium iron phosphate compound.

5. The secondary battery according to claim 4, characterized in that: The 400ppm≤Ti2-Ti1≤1000ppm; And / or, the 400ppm≤V2-V1≤1200ppm.

6. The secondary battery according to claim 4, characterized in that: At least one of the following is met: (1) The molar ratio P1 of the iron element to the phosphorus element in the first positive electrode active material layer is 0.950 to 0.975; (2) the molar ratio P2 of the iron element to the phosphorus element in the second positive electrode active material layer is 0.955 to 1.000; (3) The mass percentage Ti1 of titanium in the first lithium iron phosphate compound is 200 to 5000 ppm; (4) The mass percentage of titanium Ti2 in the second lithium iron phosphate compound is 600 to 6000 ppm; (5) The mass percentage V1 of vanadium in the first lithium iron phosphate compound is 200 to 3000 ppm; (6) The mass percentage V2 of vanadium in the second lithium iron phosphate compound is 600 to 4000 ppm.

7. The secondary battery according to claim 1, characterized in that: The single-side thickness of the first positive electrode active material layer is 10 to 60 μm; And / or, the second positive electrode active material layer has a thickness of 10 to 60 μm.

8. The secondary battery according to claim 1, characterized in that: The difference between the compaction density PD2 of the second positive electrode active material layer and the compaction density PD1 of the first positive electrode active material layer is 0.1 g / cm 3 ≤PD2-PD1≤0.15g / cm 3 .

9. The secondary battery according to claim 8, characterized in that: The compaction density PD1 of the first positive electrode active material layer is 1.50 to 3.00 g / cm 3 ; and / or, the compaction density PD2 of the second positive electrode active material layer is 1.60 to 3.15 g / cm 3 .

10. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery

    CN114068920A

  • Secondary battery and preparation method thereof

    CN115513515A

  • Positive plate, lithium ion battery and energy storage equipment

    CN116470005A

  • Lithium manganese iron phosphate battery with high safety and high energy density

    CN117276471A

  • Electrochemical apparatus and electronic apparatus comprising same

    WO2024138765A1